Proton-responsive annunciator based on i-motif DNA structure modified metal organic frameworks for ameliorative construction of electrochemical immunosensing interface - Feng, Jiejie; Yao, Tao; Chu, Changshun; Ma, Zhanfang; Han, Hongliang (Journal of colloid and interface science, 2022)
I-motif DNA structure functionalized UIO-66-NH2 can responsively release the locked methylene blue to indicate the content of tumor marker when it was placed in an acidic environment. The acidic condition was generated by the aerobic oxidation of glucose that was catalyzed with ZIF-8@GOx immunoprobe. [Display omitted] •A proton responsive annunciator based on UIO-66-NH2 was fabricated.•UIO-66-NH2 encapsulated methylene blue was functionalized with i-motif DNA.•Reformative UIO-66-NH2 can release methylene blue in an acidic solution. Reformative exploitation for metal organic frameworks (MOFs) has been a topic subject in electrochemical sensing, in which the loading of electroactive species is always introduced to enable them to generate electrochemical signal. However, insulation shielding of MOFs and flimsy combination method interfere with the signal readout of electroactive dyes when they are co-immobilized on electrode surface, indicating that an amelioration is imperatively proposed to solve these issues. Herein, a proton-activated annunciator for responsive release of methylene blue (MB) based on i-motif DNA structure modified UIO-66-NH2 was presented to design electrochemical immunosensor (Squamous cell carcinoma antigen was used as the model analyte). With the catalysis of a ZIF-8 immunoprobe contained glucose oxidase (GOx) to glucose in test tube, protons are produced in ambient solution and then they can be used as the key to unlock the i-motif functionalized UIO-66-NH2, releasing the loaded MB molecules to be readout on an improved electrode. This stimuli-responsive mode not merely eliminates the insulation effect of MOFs but also provides a firm loading method for electroactive dyes. Under the optimal conditions, the proposed immunoassay for SCCA had displayed excellent performance with a wide linear range from 1 µg mL−1 to 1 pg mL−1 and an ultralow detection limit of 1.504 fg mL−1 (S/N = 3) under the optimal conditions.